Pragilling Cooling Technique on Quality Characteristics of Milled Rice based on Cooling Temperature and Duration - Adam Bramantara Putra; Erik Cahyono (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the effect of temperature, duration of cooling, and physical quality of rice that is influenced by pragiling refrigeration technique. The resultsshowed a decrease of moisture content in the process of drying of impari varieties (22.4% -13.4%) and cisadane varieties (25% -14.3%). Dry shrinkage occurs due to the amount of water that evaporates during the drying process on the 16 kg varieties of impari and cisadane varieties of 21 kg. In addition to the varieties of grain milled rice varieties also affected by the characteristics of grain quality, the varieties of impari obtained average (52.40 ± 3.23%) while in cisadane varieties obtained average (54.54 ± 1.2%). Visual appearance, color degree measurement (Lab *) of milled rice with pragiling and non cooling cooling technique has no significant effect on the given treatment. In the analysis of quality characteristics of rice with pragiling cooling technique, the quality of rice produced is better than non-coolant treatment this is seen from the percentage of head grains, broken grains and groats that produced reached 87.68%. This is in accordance with the analysis data of variance where temperature has significant effect (0.00 <0.05) on the four temperatures used. The cooling time had a significant effect on the physical quality of rice produced with significance value (0.00 <0.05) at three time levels used.